Speaking Success in EFL Classrooms: How Self-Efficacy and Self-Regulated Learning Shape Learners’ Oral Performance - Lesta Mega; Mahdum; Supriusman; Jismulatif (VELES Voices of English Language Education Society, 2026)
Speaking proficiency is a fundamental component of communicative competence in EFL contexts, yet many Indonesian students continue to experience difficulties in oral performance. This study investigated the contribution of self-efficacy and self-regulated learning to the speaking performance of eleventh-grade students at four Madrasah Aliyah Negeri (MAN) schools in Pekanbaru. Using a correlational quantitative design, data were collected from 106 students selected via cluster random sampling. The instruments consisted of two adapted questionnaires measuring self-efficacy and self-regulated learning, and a rubric-based speaking test assessing vocabulary, fluency, comprehension, grammar, and accent. The data were analyzed using multiple linear regression after meeting the required assumptions of normality, linearity, and multicollinearity. The results showed that both self-efficacy and self-regulated learning made significant positive contributions to speaking performance, with self-efficacy (β = 0.444, t = 5.895, p < 0.001) and self-regulated learning (β = 0.534, t = 7.102, p < 0.001) emerging as significant predictors. The model produced an R value of 0.792 and an R² value of 0.627, indicating that the two predictors explained 62.7% of the variance in students’ speaking scores. These findings suggest that students with greater confidence in their speaking ability and a stronger capacity to plan, monitor, and evaluate their learning tend to demonstrate higher speaking performance. The study suggests that pedagogical practices that promote learners’ confidence and self-regulated learning may support the development of speaking proficiency in EFL classrooms.